FRI0487 Serum interleukin-6 levels in antineutrophil cytoplasmic antibody-associated vasculitis. (12th June 2018) - Berti, A.; Warner, R.; Johnson, K.; Cornec, D.; Schroeder, D.; Kabat, B.; Langford, C.A.; Hoffman, G.S.; Kallenberg, C.G.; Seo, P.; Spiera, R.; St. Clair, W. E.; et al.
Abstract : Background: The deregulated overproduction of interleukin (IL)−6 has been implicated in several inflammatory and antibody-mediated autoimmune diseases. Objectives: To investigate serum IL-6 levels (sIL-6) during active disease, remission, and relapse in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), and to explore the association of changes in sIL-6 with repopulation of blood B cells and disease relapse. Methods: sIL-6 levels (explanatory variable) were measured longitudinally over 18 months in 78 patients with AAV enrolled in a prospective, double-blinded, randomised, control trial comparing treatment with rituximab (RTX) (n=45) or cyclophosphamide (CYC)/azathioprine (AZA) (n=33). Outcome variables included baseline clinical features, ANCA type and titers, disease activity (status of active disease versus complete remission (CR)), time to B cell repopulation, relapse and severe relapse. Results: Baseline sIL6 levels were detectable (>0.49 pg/ml) in 81% of patients. At baseline, s IL-6 positively correlated with proteinase (PR3)-ANCA levels (rs =0.36, p<0.01), but not with myeloperoxidase (MPO)-ANCA levels (rs =−0.17, p=0.47). Higher baseline sIL-6 levels were associated with the presence of fever, pulmonary nodules/cavities, PR3-ANCA, and absence of renal involvement (p<0.05 for all comparisons). The median sIL-6 level was higher at baseline and promptly declined with induction therapy at following time-points (baseline, median [25%>75% IQR], 2.66 [0.76–20.98]; month 6th, 0.49 [0.49–1.16]; p<0.01) in a similar fashion in both treatment arms. An increase in sIL-6 during clinical remission was a predictor for subsequent severe relapse in RTX-treated patients (Hazard Ratio (HR) 7.24, p=0.01), but not in CYC/AZA-treated patients (HR 0.62, p=0.50). In RTX-treated B cell depleted patients (CD19 +B cell/microliter<10), the rise of sIL-6 levels did not precede B cell reappearance, regardless of whether a cut-off of ≥10 CD19+B cell/microliter (HR=0.97; p=0.97) or of ≥69 CD19+B cell/microliter (HR=1.50; p=0.41) was considered. Eighty percent of the patients who subsequently had a severe relapse in the RTX arm had B cell redetection before or at the time of the IL-6 increase, with a mean time between the redetection of B cells and sIL-6 increase of 55 days (25%>75%IQR: 0–184.25; range 0–210 days). Conclusions: At baseline, sIL-6 correlates with PR3-ANCA titers and associates with the presence of fever and pulmonary nodules/cavities. A rise in sIL-6 levels after complete remission is associated with subsequent severe relapse only in RTX-treated patients. The observed discrepancies between treatments deserve confirmation and further study. References: [1] Nishimoto N, et al. Interleukin 6: from bench to bedside. Nat Clin Pract Rheumatol. 2006;2(11):619–26. [2] Stone JH, et al. Rituximab versus cyclophosphamide for ANCA-associated vasculitis. The New England journal of medicine2010;363(3):221–32. Disclosure of Interest: None declared